Schlafens Can Put Viruses to Sleep - Eui Tae Kim; Matthew D. Weitzman (Viruses, 2022)
The Schlafen gene family encodes for proteins involved in various biological tasks, including cell proliferation, differentiation, and T cell development. Schlafens were initially discovered in mice, and have been studied in the context of cancer biology, as well as their role in protecting cells during viral infection. This protein family provides antiviral barriers via direct and indirect effects on virus infection. Schlafens can inhibit the replication of viruses with both RNA and DNA genomes. In this review, we summarize the cellular functions and the emerging relationship between Schlafens and innate immunity. We also discuss the functions and distinctions of this emerging family of proteins as host restriction factors against viral infection. Further research into Schlafen protein function will provide insight into their mechanisms that contribute to intrinsic and innate host immunity.